Relationships between gas field development and the presence and abundance of pygmy rabbits in southwestern Wyoming. Issue 5 (15th May 2017) - Germaine, Stephen S.; Carter, Sarah K.; Ignizio, Drew A.; Freeman, Aaron T.
Abstract: More than 5957 km 2 in southwestern Wyoming is currently covered by operational gas fields, and further development is projected through 2030. Gas fields fragment landscapes through conversion of native vegetation to roads, well pads, pipeline corridors, and other infrastructure elements. The sagebrush steppe landscape where most of this development is occurring harbors 24 sagebrush‐associated species of greatest conservation need, but the effects of gas energy development on most of these species are unknown. Pygmy rabbits ( Brachylagus idahoensis ) are one such species. In 2011, we began collecting three years of survey data to examine the relationship between gas field development density and pygmy rabbit site occupancy patterns on four major Wyoming gas fields (Continental Divide–Creston–Blue Gap, Jonah, Moxa Arch, Pinedale Anticline Project Area). We surveyed 120 plots across four gas fields, with plots distributed across the density gradient of gas well pads on each field. In a 1 km radius around the center of each plot, we measured the area covered by each of 10 gas field infrastructure elements and by shrub cover using 2012 National Agriculture Imagery Program imagery. We then modeled the relationship between gas field elements, pygmy rabbit presence, and two indices of pygmy rabbit abundance. Gas field infrastructure elements—specifically buried utility corridors and a complex of gas well pads, adjacent disturbed areas, and well pad access roads—were negatively correlated with pygmy rabbit presence and abundance indices, with sharp declines apparent after approximately 2% of the area consisted of gas field infrastructure. We conclude that pygmy rabbits in southwestern Wyoming may be sensitive to gas field development at levels similar to those observed for greater sage‐grouse, and may suffer local population declines at lower levels of development than are allowed in existing plans and policies designed to conserve greater sage‐grouse by limiting the surface footprint of energy development. Buried utilities, gas well pads, areas adjacent to well pads, and well pad access roads had the strongest negative correlation with pygmy rabbit presence and abundance. Minimizing the surface footprint of these elements may reduce negative impacts of gas energy development on pygmy rabbits.